2005
DOI: 10.1007/s11664-005-0101-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced gettering of iron impurities in bulk silicon by using external direct current electric field

Abstract: Iron impurities in bulk silicon are found to getter efficiently at the polysilicon layer by an electric field during isothermal annealing. Experimental results show that iron concentration at the polysilicon layer increases to the level that becomes detectable by total reflection x-ray fluorescence (TXRF) spectroscopy. The improved gettering efficiency for iron is attributed mainly to the directional drift of ionic iron interstitials toward the polysilicon gettering sites, under the influence of the applied po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…TXRF was used to monitor Fe and Cu in bulk silicon: Lee et al 140 found that the getter efficiency of Fe impurities in bulk silicon was improved by applying an electric field during isothermal annealing of the polysilicon layer. They reported this to be an effective method for reducing the iron content in silicon.…”
Section: Txrfmentioning
confidence: 99%
“…TXRF was used to monitor Fe and Cu in bulk silicon: Lee et al 140 found that the getter efficiency of Fe impurities in bulk silicon was improved by applying an electric field during isothermal annealing of the polysilicon layer. They reported this to be an effective method for reducing the iron content in silicon.…”
Section: Txrfmentioning
confidence: 99%